An Analysis of Moral Values and Character Education in 'Wonder' Movie - Dinda, Dinda Ayu Saputri; Chotimah, Chusnul; Amanda, Hana (E-Link Journal, 2025)
The title of this research is An Analysis of Moral Values and Character Education Depicted in the Film Wonder. This research addresses the issue of declining moral values among youth, as reflected in the increasing prevalence of bullying and intolerance in educational settings. This research aims to examine how the 2017 film Wonder can be utilized as a medium for teaching moral values and character education. Specifically, the study investigates how selected scenes, character dialogues, and interactions portray ethical principles and personal virtues. Descriptive qualitative method and content analysis are used as a research method; the data were categorized and interpreted through Eyre’s framework, which outlines eleven core moral values and Lickona’s theory of character education, which emphasizes the development of virtues such as empathy, courage, and respect in formal learning contexts. Data were collected by analyzing the film’s script and narrative structure, identifying key moments where moral and character values were evident. The analysis reveals that Wonder frequently portrays values such as respect, self-confidence, and love, with empathy emerging as the most dominant character trait. These findings suggest that films like Wonder can be effectively integrated into classroom instruction to foster moral reasoning, empathy, and emotional intelligence, thus supporting the development of ethically aware and socially responsible learners.